2007
DOI: 10.1038/sj.bmt.1705673
|View full text |Cite
|
Sign up to set email alerts
|

Safety of vaccinating sibling donors with live-attenuated varicella zoster vaccine before hematopoietic stem cell transplantation

Abstract: Reactivation of varicella zoster virus (VZV), clinically manifested as herpes zoster (HZ) is a common complication after hematopoietic stem cell transplantation (HSCT). The optimum prophylaxis for this disease has not been defined. In this study, we examined the effects of vaccinating donors with a live-attenuated vaccine with particular reference to their immune responses and the outcome of HSCT patients. Forty prospective HLAmatched sibling donors were vaccinated before HSCT. There were humoral immune respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…HZ is a very common complication following HSCT [170, 774]. Long-term prophylaxis with low-dose aciclovir [775778] or valaciclovir [779] significantly reduces the incidence of VZV reactivation and serious complications, and is recommended for the duration of immunotherapy and continuing through 1 year after HSCT [776, 778].…”
Section: Management and Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…HZ is a very common complication following HSCT [170, 774]. Long-term prophylaxis with low-dose aciclovir [775778] or valaciclovir [779] significantly reduces the incidence of VZV reactivation and serious complications, and is recommended for the duration of immunotherapy and continuing through 1 year after HSCT [776, 778].…”
Section: Management and Preventionmentioning
confidence: 99%
“…A case of recurrent HZO cured by varicella vaccination was also reported [786]. In studies that evaluated live-attenuated VZV vaccine in HSCT [774, 787], Oka/RIT (Varilrix™ Glaxo-SmithKline Biologicals, Rixensart, Belgium) was safe but poorly immunogenic. A systematic review concluded that although inactivated VZV vaccine may reduce HZ severity in stem cell transplant recipients, more research was required [788].…”
Section: Management and Preventionmentioning
confidence: 99%
“…133 Although initial reports of the administration of heatinactivated live attenuated varicella vaccine to SCT recipients were encouraging, 134,135 this approach has not yet been further developed.…”
Section: Varicella Vaccinementioning
confidence: 99%
“…Our strategy is to provide sufficient CMV immunity to HCT recipients by vaccinating their immunocompetent donors [18][19][20]. Studies have shown that by immunizing the donor pre-HCT, it is possible to transfer vaccine-specific immunity to the recipient [20][21][22][23].…”
mentioning
confidence: 99%